Analisis Problematika Perekrutan Kelompok Penyelenggara Pemungutan Suara (KPPS) pada Pemilihan Walikota dan Wakil Walikota Medan Tahun 2020 - Panataran Saut Maruli Tua Marpaung; Hendra Harahap; Hatta Ridho (Universitas Medan Area, 2022)
This paper intends to discuss what is problematic in the recruitment of KPPS members and how recruitment management is carried out by the Medan City KPU to meet the needs of KPPS members. The method used is qualitative. The research is located in Medan Tembung District, with research subjects namely members of KPPS, KPU, PPS, KPPS, PPK and voters. The data collection process is by interview, documentation and observation. The analysis used is content analysis. The problem with the extension of the recruitment of KPPS members is due to the implementation of the stages of recruiting KPPS members that are not in accordance with the rules. The Voting Committee (PPS) does not announce the registration of KPPS members but continues the recruitment to the Head of the Environment. The implementation of the recruitment management function was not going well and the control over the ad hoc agency was very weak, causing the recruitment of KPPS members to be carried out by the Head of the Environment. KPU needs to carry out political education programs in collaboration with academics and the government and the recruitment of KPPS members in the future requires a new pattern in order to create KPPS members who are independent and with integrity.